Entrepreneur Hubris, Organizational Ambidexterity, and Dynamic Capability Construction - Guo, Yan; Huang, Pei-Wen; Ciu, Chu; Fang, Shih-Chieh; Tsai, Fu-Sheng (Frontiers in Psychology, 2022)
This paper demonstrated the influences of initiation, development, turn-down, and re-initiating of dynamic capability of an entrepreneurial firm in solar energy industry. The focus is on the impact of entrepreneurial hubris, which may affect the decision of ambidexterity that can vitalize dynamic capability. The findings indicated that, when the major decision maker (the founder entrepreneur) has the trait of hubris, the decision making process may be overly arbitrary and a decision of being exploratory or exploitative alone is likely to be made. On the contrary, when founder entrepreneur is aware of the hubris and shares the decisive power, the decision of being ambidextrous as a dynamic capability is more freely to be achieved. This paper contributes by discovery of the cognitive-based micro-foundation of entrepreneurial ventures and linkage of such micro-foundation to organizational ambidexterity.